Information system for extreme rain index prediction and potential flood warning based on rain radar in Jakarta area - Hidayatullah, Muhammad Faisal; Pratama, Rama; Sya’bani, Taufiq Salman; Ahmad, Umar Ali; Awaludin, Asif; Darmawan, Syukri; Komarudin, Rudy (Universitas Telkom, 2025)
In Indonesia, significant variations in rainfall are a severe challenge, especially in the Special Capital Region (DKI) Jakarta, which is very vulnerable to flooding and the effects of climate change compared to other coastal areas in Southeast Asia. This flood caused considerable losses to society, industry, and government. Inaccurate predictions of rainfall lead to difficulties in anticipating floods and landslides, causing an expansion of the impact of these disasters. Therefore, a solution such as